The clustering and evolution of Hα emitters at z ∼ 1 from HiZELS - Sobral, D; Best, P; Geach, J; Smail, I; Cirasuolo, M; Garn, T; Dalton, G; Kurk, J (2010)
The clustering properties of a well-defined sample of 734 Hα emitters at z= 0.845 ± 0.015, obtained as part of the Hi-z Emission Line Survey, are investigated. The spatial correlation function of these Hα emitters is very well described by the power-law ξ = (r/r0)-1.8, with a real-space correlation, r0, of 2.7 ± 0.3 h-1 Mpc. The correlation length r0 increases strongly with Hα luminosity (LHα), from r0 ∼ 2 h-1 Mpc for the most quiescent galaxies [star formation rates (SFRs) of ∼4 M⊙ yr-1] up to r0 > 5 h-1 Mpc for the brightest galaxies in Hα. The correlation length also increases with increasing rest-frame K-band (MK) luminosity, but the r0-LHα correlation maintains its full statistical significance at fixed MK. At z = 0.84, star-forming galaxies classified as irregulars or mergers are much more clustered than discs and non-mergers, respectively; however, once the samples are matched in LHα and MK, the differences vanish, implying that the clustering is independent of morphological type at z ∼ 1 just as in the local Universe. The typical Hα emitters found at z = 0.84 reside in dark matter haloes of ≈1012 M⊙, but those with the highest SFRs reside in more massive haloes of ≈1013 M⊙. The results are compared with those of Hα surveys at different redshifts: although the break of the Hα luminosity function L*Hα evolves by a factor of ∼30 from z= 0.24 to 2.23, if the Hα luminosities at each redshift are scaled by L*Hα(z) then the correlation lengths indicate that, independently of cosmic time, galaxies with the same (LHα)/L*Hα(z) are found in dark matter haloes of similar masses. This not only confirms that the star formation efficiency in high redshift haloes is higher than locally but also suggests a fundamental connection between the strong negative evolution of L*Hα since z = 2.23 and the quenching of star formation in galaxies residing within dark matter haloes significantly more massive than 1012 M⊙ at any given epoch. © 2010 The Authors. Journal compilation © 2010 RAS.